Mobile banking as business strategy: Impact of mobile technologies on customer behaviour and its implications for banks - Rajnish Tiwari; Stephan Buse; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2006)
Mobile Commerce is gaining increasing acceptance amongst various sections of the society. This growth can be partly traced back to technological and demographical developments that have been influencing important aspects of the socio-cultural behaviour in today's world. The need/wish for mobility seems to be the driving force behind Mobile Commerce in general. Mobile Banking, availment of bank-related financial services via mobile devices, builds a cornerstone of Mobile Commerce. An empirical survey of customer acceptance conducted within the frame of our research clearly reveals a major, growing interest in Mobile Banking. However, since the degree of interest and the willingness to pay vary for individual services, it seems to be necessary to design specific services taking the needs and wishes of relevant target groups into consideration. Banks ought to therefore employ mobile channels with a clear business-focus. This paper examines the opportunities for banks to generate revenues by offering value-added, innovative mobile financial services while retaining and even extending their base of technology-savvy customers.
urn:nbn:de:gbv:830-opus-3308
Keywords: 650; Mobile Commerce; Mobile Banking; Mobile Financial Services; Multi-channel Strategy